Short‐term outcomes of robot‐assisted minimally invasive esophagectomy with extended lymphadenectomy for esophageal cancer compared with video‐assisted minimally invasive esophagectomy: A single‐center retrospective study. Issue 2 (12th October 2021) - Morimoto, Yosuke; Kawakubo, Hirofumi; Ishikawa, Aiko; Matsuda, Satoru; Hijikata, Nanako; Ando, Makiko; Mayanagi, Shuhei; Irino, Tomoyuki; Nakamura, Rieko; Wada, Norihito; Tsuji, Tetsuya; Kitagawa, Yuko
Abstract: Background: The safety and feasibility of robot‐assisted minimally invasive esophagectomy (RAMIE) remain unclear. The aim of this study was to compare the short‐term outcomes of RAMIE with extended lymphadenectomy and conventional minimally invasive esophagectomy (MIE) in order to investigate the safety and feasibility of RAMIE. Methods: A retrospective analysis of 87 patients who underwent minimally invasive esophagectomy at our institution between April 2018 and March 2020 was made, assigning 22 in the RAMIE group and 65 in the MIE group. Short‐term clinical outcomes and clinical baseline data were compared. Results: The baseline characteristics were comparable. No significant difference in median thoracic phase blood loss and median number of dissected mediastinal lymph nodes were observed. The median operative time of thoracic approach was significantly longer in the RAMIE group than the MIE group (305 minutes [221–397] vs 227 minutes [133–365], P < .0001). With respect to postoperative complications such as recurrent laryngeal nerve paralysis (Clavien–Dindo ≥ grade II) (RAMIE 4.6% vs MIE 17%, P = .11) and postoperative pneumonia (Clavien–Dindo ≥ grade III) (RAMIE 9% vs MIE 23%, P = .13), no significant difference was observed. The patients in the RAMIE group had a better postoperative swallowing function ( P = .023) and were able to start oral food intake significantly earlier ( P = .007). The median hospital stay was significantly shorter in the RAMIE group than in the MIE (23 days vs 35 days, P = .009). Conclusions: RAMIE with extended lymphadenectomy was safe and feasible for esophageal cancer and resulted in improved postoperative swallowing function and shorter postoperative hospital stay.